Xác định thời gian đánh bóng hạt ở máy đánh bóng ĐB-1 - Lê, Công Huỳnh (Bộ Giáo dục và Đào tạo, 2013)
Grain polishing time T has been idetified by the moving time of grains along length L of polishing chamber. Based on the obtained polishing time, reasonabble length of polishing chamber will be determined, in order to in sure high output of polishing machines and good quality of polished products.